Accelerated Molecular Statics Based on Atomic Inertia Effect (Communications in Computational Physics, 2020)
Molecular statics (MS) based on energy minimization serves as a useful simulation technique to study mechanical behaviors and structures at atomic level. Theefficiency of MS, however, still remains a challenge due to the complexity of mathematical optimization in large dimensions. In this paper, the Inertia Accelerated MolecularStatics (IAMS) method is proposed to improve computational efficiency in MS simulations. The core idea of IAMS is to let atoms move to meta positions very close totheir final equilibrium positions before minimization starts at a specific loading step.It is done by self-learning from historical movements (atomic inertia effect) withoutknowledge of external loadings. Examples with various configurations and loadingconditions indicate that IAMS can effectively improve efficiency without loss of fidelity. In the simulation of three-point bending of nanopillar, IAMS shows efficiencyimprovement of up to 23 times in comparison with original MS. Particularly, the size-independent efficiency improvement makes IAMS more attractive for large-scale simulations. As a simple yet efficient method, IAMS also sheds light on improving theefficiency of other energy minimization-based methods.